Analgesic, anti-inflammatory and venotonic effects of Cissus quadrangularis Linn - Panthong A. (2014)
Cissus quadrangularis, a medicinal plant indigenous to Asia and Africa, is used for many ailments, especially for the treatment of hemorrhoid. The effects associated with hemorrhoid, i.e. analgesic and anti-inflammatory activities as well as the venotonic effect of the methanol extract of C. quadrangularis (CQ) were assessed in comparison with reference drugs. In the analgesic test, CQ provoked a significant reduction of the number of writhes in acetic acid-induced writhing response in mice. CQ also significantly reduced the licking time in both phases of the formalin test. The results suggest peripheral and central analgesic activity of CQ. In acute phase of inflammation CQ elicited the inhibitory effect on the edema formation of the rats' ear induced by ethyl phenylpropiolate as well as on the formation of the paw edema in rats induced by both carrageenin and arachidonic acid. It is likely that CQ is a dual inhibitor of arachidonic acid metabolism. In addition, CQ exerted venotonic effect on isolated human umbilical vein similarly to the mixture of bioflavonoids, i.e. 90% diosmin and 10% hesperidin. The results obtained confirmed the traditional use of C. quadrangularis for the treatment of pain and inflammation associated with hemorrhoid as well as reducing the size of hemorrhoids.